Effectiveness of an ergonomic chair intervention in reducing low back pain among informal garment workers: A Quasi-Experimental Study - Sumardiyono; Fauziah, Fathiyatur Rohmah (International Journal of Occupational Safety and Health, 2026)
Introduction: Garment workers have low back pain (LBP) which impacts their productivity and health because they sit a lot and use non-ergonomic chairs. This was done by evaluating the effectiveness of ergonomic chairs among small scale garment workers in the reduction of LBP. Methods: The quasi-experimental pretest-posttest control group design was employed in which 102 sewing workers of micro and small-scale garment industries were used in Tuban Lor Village, Karanganyar Regency. The sample was divided into intervention (n= 51 ) and control (n= 51 ) groups. The intervention was in the form of an ergonomic chair that was developed along anthropometric measures of workers. On day 0, 7, and 14 Oswestry Disability Index (ODI) and Rapid Upper Limb Assessment (RULA) were used to measure LBP intensity and posture. Repeated Measures ANCOVA/One-Way ANCOVA were used to analyze data after adjusting it by age, gender, BMI and years of service. Results: It significantly decreased LBP scores time dependently in the intervention group (F=6.289, p=0.003) with an apparent linear trend (p=0.002), but not in the control group (p=0.390). Significant group differences were found at day 7 and 14 (p=0.001) and not at baseline (p=0.731). Covariates did not create any significant effect. There was also an improvement in posture scores in form of improved RULA scores. Conclusion: Within 14 days, ergonomic chair intervention was successful in reducing low back pain and increasing the posture of informal garment workers.